The lesson of a savage (Journal of Parents and Teachers, 1996)
Indian Chief Seattle, in his 1854 letter, rejects the purchase of Indian lands, stressing their spiritual and sacred connection to nature. He criticizes the idea that land can be bought or sold, emphasizing its cultural importance. The letter is a testimony of indigenous resistance to colonization and their profound relationship with their environment.
Keywords: spiritual connection; nature; colonization